Russian wheat aphid biotypes in Lesotho: distribution, impact on wheat production and the role of phytohormones in host resistance - Masupha, Pitso Victor (University of the Free State, 2019)
Lesotho has over the years been experiencing a decline in wheat yield. The dynamic nature, rapid shifts in the environment, and devastating impacts of Russian wheat aphid (RWA) likely contribute to the low wheat yields in Lesotho. The study aims to investigate RWA biotypic diversity, distribution, impact on yield and the role of phytohormones in Lesotho farmers’ cultivars and those imported from South Africa, in the mountains and lowlands districts of Lesotho. The status of RWA distribution and diversity in Lesotho was evaluated by collecting and analysing samples from wheat fields in parts of Mokhotlong, Thaba Tseka, Maseru and Leribe. Aphid samples were cloned and screened for biotype status at the ARC-SG greenhouses (Bethlehem, South Africa). Our results revealed that four of the five South African biotypes, RWASA1 – 4, also exist in Lesotho. We further investigated the reaction of some of the farmers’ wheat cultivars (Bolane and Makalaote) and South African dryland cultivars grown in Lesotho to RWA infestation. This part of the study occurred under greenhouse conditions where different biotypes (RWASA1 – 4) artificially infested the cultivars. A damage rating scale evaluated induced damage, and the Lesotho farmers’ cultivars Bolane and Makalaote expressed susceptibility to all four biotypes except Bolane, which conferred medium resistance to RWASA2. Similar cultivar evaluations under natural infestation were carried out under field conditions in the mountains and lowlands of Lesotho. In contrast to the greenhouse results, both Makaote and Bolane expressed medium susceptibility; however, Bolane yielded lower than all other cultivars in almost all sites. Despite the reaction to aphids, Makalaote a relatively fast-grower escaped peak periods of RWA infestation and outperformed most of the South African cultivars. The underlying resistance mechanism of these wheat genotypes was investigated by determining some of the induced biochemical changes during RWA infestation. In this regard, three cultivars (Bolane, Elands and PAN3379) with differential resistance to RWA (RWASA1 and 3) were evaluated. Biotype 1 infestation did not induce any of the pathogenesis-related enzyme activities (GLC and POD) or defence related enzymes (LOX and PAL) associated with biosynthesis of hormones in Bolane. However, RWASA3 infestation induced all the enzymes except GLC. In agreement with the phenotypic studies, RWASA1 but not RWASA3, induced all enzyme activities in Elands. The two biotypes induced almost all the enzyme activities in PAN 3379, except GLC, which did not respond to RWASA1 infestation. The involvement of defence modulating hormones salicylic, jasmonic and absiscic acids during the resistance response was also studied. In contrary to our expectations, RWA- induced PAL and LOX activities in Bolane did not positively correlate with salicylic or jasmonic acid accumulation, and no increases in absiscic content were recorded. According to phenotypic studies, PAN 3379 confers medium resistance to RWASA1 and resistance to RWASA3, and we anticipated some shortfall in the accumulation of one or two hormones. Levels of RWASA1-induced LOX activity did not elicit jasmonic acid accumulation, but PAL activity led to higher salicylic and absiscic acids content. Biotype 3 activated accumulation of all the three hormones. Phenotypic studies show Bolane as susceptible to RWASA3, however induction of some defence enzymes in Bolane mandates additional studies that could elucidate defences determining resistance in wheat. Additionally, the biochemical studies could be complemented by full metabolite profiling during plant-aphid interaction. Perhaps some metabolite combinations could assist in elucidating the resistance mechanisms to aphid infestations and provide a clue to differential responses to the different biotypes.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2019
Keywords: Biotypes; Russian wheat aphid; β-1,3-Glucanase; Peroxidase; Lipoxygenases; Phenylalanine ammonia-lyase; Salicylic acid; Jasmonic acid and Absiscic acid; Wheat - Diseases and pests; Wheat - Insect resistance - Lesotho; Russian wheat aphid - Lesotho